PEMANFAATAN MESIN PENCETAK PAKAN AYAM DALAM USAHA MENINGKATKAN PRODUKTIVITAS PETERNAKAN AYAM DI DESA PERGAM KECAMATAN AIRGEGAS - Eka Sari Wijianti; Saparin Saparin; Yudi Setiawan; Okto Supratman; Jeri Ariksa; Okto Supratman (Fakultas Teknik, Universitas Bangka Belitung, 2022)
Community service (PkM) has been carried out regarding the use of chicken feed printing machines. The PkM place is in Pergam Village, Airgegas District, South Bangka Regency. The purpose of PkM is to increase the productivity of the Pergam village partner chicken farms. This program has been implemented before in other areas, because the program was successfully adopted in Pergam village. This service is a continuation of the 2021 service on the use of egg incubators. The success of the hatchery program through the egg incubator raises new problems related to feed availability. Currently, the price of feed is expensive, so farmers must look for alternatives to meet their feed needs. Service partners have limited funds to buy feed from the market. So the service team from the University of Bangka Belitung provided assistance in the form of a chicken feed printing machine. The implementation of the service has been carried out through four stages, including: The first stage, field observations and interviews with partners to record the problems faced by partners. The second stage, determine the focus and solution to the problem. The third stage is the implementation of service and assistance in the use of chicken feed printing machines, and the last is an evaluation of activities to record problems and the sustainability of the service program in the future. The service that has been carried out is by handing over two units of feed printing machines, assistance with supporting equipment for livestock and machinery. based on the results of interviews with partners, with a chicken feed printing machine can reduce feed costs by 50-60%.